Vegetation Dynamics, Types of Species, Plant Density. - Nasution, Yusnita Anwar; Rafeah, Husni; Mtd, Nur Asiah; Bella, Khairani (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to observe the process of vegetation succession in the Campus Park area, Old Building STAIN Mandailing Natal, Faculty of Tarbiyah, and Keguruan Science, focusing on changes in vegetation types that occur during observation and factors that influence the course of succession. The research was conducted using a quantitative observation method, in which data were collected through field surveys by laying plots in parallel. Data collected included species type, dominance analysis, density measurement, relative density, and plant frequency. The results showed that Asystasia gangetica was the dominant species during the secondary succession stage, due to its high ability to colonize and adapt to disturbed environmental conditions. Besides Asystasia gangetica, other species found include Digitaria sanguinalis, Meryta latifolia, Curculigo capitulaca, Anthurium crystallinum, and Clitoria ternatea. The dominance of Asystasia gangetica is influenced by post-cultivation soil conditions, competition between species, and its ability to adapt. Climatic factors also play an important role in influencing the succession process. The practical implications of the results of this study are recommendations for increasing vegetation diversity and vegetation monitoring in the context of secondary succession.